Interdisipliner Sastra: Hubungan Antara Sastra dan Ekologi dalam Antologi Puisi Karya D. Zawawi Imron - Fauzi, Noer Moh Bahrul; Ambarwati, Ari (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study examines the relationship between literature and ecology in the poetry anthology of Sarya D. Zawawi Imron. This study uses a descriptive qualitative method with an ecocritical approach. The data source is the poetry anthology Bantalku Pmbak Blanket My Wind. Primary data in the form of poetry excerpts that have ecological elements. Secondary data in the form of literature studies, articles, books, etc. The data analysis technique uses the note-taking technique where the researcher is the initial instrument. The data collection technique is carried out by reading poetry related to nature which includes grouping, data processing, and data conclusions. The results of the study show that poetry can raise environmental issues that can make people aware. Through the poetry anthology Bantalku Ombak Blanket My Wind provides a real picture that nature has an important role as the main source in human life. In this case, D. Zawawi Imron’s poetry has succeeded in criticizing how the Madurese people are aware of their environment so that they can utilize the land to be managed properly, natural resources such as salt which is a core source for the Madurese people, or the dependence of life on the sea. Through an interdisciplinary approach, such as the analysis of poetry by D. Zawawi Imron, it can be seen that literature can be an effective means of conveying environmental messages and inspiring concern for environmental sustainability.